Parameterizing the AquaCrop model for potato growth modeling in a semi-arid region - Ahmadi, Seyed Hamid; Reis Ghorra, Mohammad Reza; Sepaskhah, Ali Reza (Field crops research, 2022)
The AquaCrop model was used to model potato growth in a hot semi-arid environment under diverse irrigation managements including water saving irrigation treatments in two growing seasons of 2012 and 2013. The potato cultivars were Agria and Ramos in 2012, and Agria and Sante in 2013. The irrigation treatments were full irrigation and different static and dynamic deficit irrigation managements. The model was calibrated with the data of the cultivar Agria under full irrigation and static deficit irrigation in 2013. Validation was performed using the data from the other potato cultivars and growing seasons, by keeping the conservative crop parameters adjusted in calibration and changing those non-conservative parameters referring to the crop development. Analysis showed that biomass simulation was highly affected by the normalized water productivity (WP*). Unlike the previous studies on modeling with AquaCrop that assumed only one WP* for the whole growing period, we found that it is required to calibrate one WP* for the first half of the growing season until flowering, and then recalibrated WP* for the late growing season. One single WP* assumed for the whole growing season could not simulate the declining potato growth at the late growing season satisfactory, when potatoes were subject to water stress and high air temperature (heat stress). The simulations of the calibrated model showed that the model could simulate total soil water content, volumetric soil water content, and tuber dry yield satisfactory. In addition, the model showed excellent performance in simulation of the total actual evapotranspiration and end-season water productivity. The AquaCrop model was good in simulating the in-season biomass, though it showed fair simulation of biomass in the late growing season. Overall, the performance of the AquaCrop model was reasonable and satisfactory, and the model is a reliable analytical tool for irrigation water management and proper decision making in potato production under variable water resources in the hot semi-arid areas. •AquaCrop has been used for modeling potato growth in a hot and semi-arid region.•AquaCrop had satisfactory performance in simulating soil water content and tuber dry yield.•AquaCrop had excellent performance in simulating end-season actual evapotranspiration and water productivity.•Two WP* values were assumed to differentiate the effects of water and heat stresses on different growing periods.•The calibrated WP* was assigned 13 and 10 g m−2 during the early and late growing season, respectively.